Antioxidant potential of the diet in Italian children with food allergies - Erica Pendezza; Chiara Nava; Alessandro Leone; Francesca Riccaboni; Alessandra Bosetti; Gian Vincenzo Zuccotti; Simona Bertoli; Simona Bertoli; Enza D’Auria (Frontiers in Nutrition, 2023)
A reduced fruit and vegetable consumption, which implies a decreased intake of antioxidant compounds, seems to play a role in allergic diseases onset. Data on the antioxidant capacity of diet in children with food allergies, who are on an avoidance diet, are still lacking. This pilot study aims to assess the antioxidant potential of diet in Italian children with food allergies, compared to healthy children, using the oxygen radical absorbance capacity (ORAC) method. 95 children (54 with confirmed food allergies and 41 controls), with a median age of 7.8 years, were enrolled and underwent a nutritional assessment. Mean nutrient intakes were compared using the Mann–Whitney test. ORAC resulted significantly lower in allergic children (median 2,908, IQR: 1450;4,716) compared to control children (median 4,392, IQR: 2523;5,836; p = 0.049). Among micronutrients with antioxidant properties, vitamin A intakes were significantly higher in controls than in allergic children. Using Spearman’s correlation, a moderate-to-strong correlation between ORAC and vitamin C, potassium and magnesium was observed (ρ = 0.648, p < 0.001; ρ = 0.645, p < 0.001; ρ = 0.500, p < 0.001, respectively). Iron, phosphorus, vitamin E and vitamin A intakes were also moderately-to-low correlated with ORAC values (ρ = 0.351, p < 0.001; ρ = 0.367, p < 0.001; ρ = 0.346, p < 0.001; and ρ = 0.295, p = 0.004, respectively). We hypothesize that the reduced antioxidant potential of the diet might be related to a reduced variety of the diet in children with food allergies. Our study suggests that the diet of children with food allergies has a lower antioxidant potential (expressed as ORAC value) compared to the diet of healthy children, regardless of the allergenic food excluded from the diet. This issue should be further investigated in prospective, powered studies.